Understanding stakeholders’ experience with sickle cell disease by social media listening across Europe - Brás, Daniel; Bento, Celeste; Asaithambi, Sathyaraj; Chauhan, Jyoti; Moital, Ines (Frontiers in Genetics, 2025)
BackgroundThe use of social media platforms for sharing health-related information is on the rise. Sickle cell disease (SCD) affects millions of people worldwide. However, discussions by SCD stakeholders on social media remain unexplored. This study aimed to analyze discussions among SCD stakeholders on social media to understand their awareness of SCD and to explore their perceptions of the patient journey, hospitalizations and complications due to SCD, the impact of the disease on quality of life (QoL), and current unmet needs by using social media listening (SML).MethodsData was retrospectively collected from April 2019 to April 2021 on SCD specific terms in 14 European countries from blogs, forums, and social networking sites (Twitter, public Facebook, YouTube, and Instagram). Advanced social media analytics tools, Talkwalker and Social Studio, were used for data aggregation and analysis. Conversations were filtered and contextualized through a 3-tier technique involving automated relevancy algorithms and manual review.ResultsOf 317.9K conversations on SCD (93% Twitter), 945 posts on relevant patient-centric conversation were analyzed. Most patients were females (73%) and ≤30 years old (75%). Patient journey stages were addressed in 52% of conversations. Patient journey conversations were mainly regarding symptoms (56%) (mainly pain episodes, pain in general, and vaso-occlusive crises) and treatment (44%). Conversations on hospital visits or hospitalization mostly revolved around crises faced due to symptoms. Impact on QoL, especially emotional impact (56%), was also extensively discussed. Unmet needs were derived from 24% of the conversations, lack of awareness of SCD (42%) and lack of empathy and support from HCPs (24%) being the most frequent topics. Patients reported having their symptoms questioned or dismissed by healthcare professionals, which they attributed to racial bias.ConclusionSML proves to be a useful tool for exploring the real experiences, concerns, and needs of SCD patients and other stakeholders. Analysis of SCD-related social media posts reveals that discussions mainly focus on symptoms, particularly pain, treatment, and the emotional impact of SCD on QoL. These insights are crucial for enhancing the management of SCD patients.